Isolation and Identification of Endophytic Fungi from Aloe vera Leaves and Chemical Analysis of the Alcoholic Extract of the Leaves Using HPLC, GC, and GC-Mass Devices - Al Nuaimy, Mohammed Ali Abdul Razzaq; Sumaiya Naeema Hawar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The study’s goals were to separate and identify endophytic fungi from Aloe vera leaves by looking at their morphology and molecules, as well as to find the chemical compounds in the leaf extract by using HPLC, GC, and GC-Mass instruments. The results showed that 53 endophytic fungi were isolated from a total of 120 pieces of A. vera leaves, with a total colonization rate of 44.16%. The fungus Aspergillus terreus had a colonization rate of 14.16%; Aspergillus niger had a colonization rate of 13.33%; Penicillium chermesinum demonstrated a colonization rate of 6.66%; Paecilomyces variotii had a colonization rate of 2.5%; Talaromyces radicus; and Aspergillus flavus achieved a colonization rate of 1.66%. Finally, the fungi Aspergillus quadrilineatus, Talaromyces verruculosus, Neoscytalidium dimidiatum, Alternaria solani, and Aspergillus niveus achieved a colonization rate of 0.83%. The results of examining the alcoholic extract of the leaves using the HPLC device showed the presence of the chemical compounds aloin at a concentration of 125.39 ppm and aloe emodin at a concentration of 66.59 ppm. We looked at the leaf alcoholic extract with a GC machine and found a group of fatty acids. These included linoleic, oleic, palmitic, and stearic. The GC-MS test revealed a group of active compounds, including Heptane, 1-(ethenylthio), Ethanedicarboxamide, N-allyl-N’-(2,5-dimethylphenyl), 2H-Pyran, 2-(3-butynyloxy) tetrahydro, 1,2-Cyclobutanedicarboxylic acid, 3-methyl-dimethyl ester and 4 (1H)-Pyrimidinone, 2-(propylthio). The presence of endophytic fungi from which effective enzymes or compounds can be isolated could probably have an important role in future medical and therapeutic uses. Also, the leaves of the A. vera plant have medicinal and therapeutic uses for many diseases.